Optimized Conformal Total Body Irradiation Among Recipients of TCRαβ/CD19-Depleted Grafts in Pediatric Patients With Hematologic Malignancies: Single-Center Experience - Kobyzeva, Daria; Shelikhova, Larisa; Loginova, Anna; Kanestri, Francheska; Tovmasyan, Diana; Maschan, Michael; Khismatullina, Rimma; Ilushina, Mariya; Baidildina, Dina; Myakova, Natalya; Nechesnyuk, Alexey (Frontiers in Oncology, 2021)
Total body irradiation (TBI) in combination with chemotherapy is widely used as a conditioning regimen in pediatric and adult hematopoietic stem cell transplantation (HSCT). The combination of TBI with chemotherapy has demonstrated superior survival outcomes in patients with acute lymphoblastic and myeloid leukemia when compared with conditioning regimens based only on chemotherapy. The clinical application of highly technological intensity-modulated radiation therapy (IMRT)-based methods (volumetric modulated arc therapy – VMAT and tomotherapy) seems to be promising and has been actively used worldwide. The optimized conformal total body irradiation (OC-TBI) method described in this study provides selected dose reduction for organs at risk with respect to the most significant toxicity (lungs, kidneys, lenses). This study included 220 pediatric patients who received OC-TBI with subsequent chemotherapy and allogenic HSCT with TCR/СВ19 depletion. A group of 151 patients received OC-TBI using TomoTherapy, and 40 patients received OC-TBI using the Elekta Synergy™ linac with an Agility-MLC (Elekta) using volumetric modulated arc therapy (VMAT). Twenty-nine patients received OC-TBI with supplemental simultaneous boost to bone marrow – (SIB to BM) up to 15 Gy: 28 pts – TomoTherapy; 1 pt - VMAT. The follow-up duration ranged from 0.3 to 6.4 years (median follow-up – 2.8 years). Overall survival (OS) for all the patients was 63% (95% Cl: 56-70), and event-free survival (EFS) was 58% (95% Cl: 51-65). The cumulative incidence of transplant-related mortality (TRM) was 10.7% (95% Cl: 2.2-16) for all patients. The incidence of early TRM (<100 days) was 5.0% (95% Cl: 1.5-8.9), and that of late TRM (>100 days) was 5.7 (95% Cl: 1.7-10.2). The main causes of death for all the patients were relapse and infection. The concept of OC-TBI using IMRT VMAT and helical treatment delivery on a TomoTherapy treatment unit provides maximum control of the dose distribution in extended targets with simultaneous dose reduction for organs at risk. This method demonstrated a low incidence of severe side effects after radiation therapy and predictable treatment effectiveness. Our initial experience demonstrates that OC-TBI appears to be a promising technique for the treatment of pediatric patients.